How Gender Inequality in Rural Area: A Movie Analysis Through Sociolinguistic Perspective: Bagaimana Ketimpangan Gender di Pedesaan: Sebuah Analisis Film Melalui Perspektif Sosiolinguistik - Muhammad Ali Sukran (LPPM Institut Studi Islam Sunan Doe, 2022)
Gender discrimination is a serious issue throughout society, particularly in the local context. Unfair treatment of women is viewed as a natural existence, and this issue is hidden by well-ingrained cultural norms. This study examines the gender discrimination that occurs in the local Sasak film